Bulk Metallic Glasses - Schroers, Jan (Physics today, 2013)
In recent decades various research groups have discovered a wide range of bulk metallic glasses (BMGs). Some are metal-metal alloys based on elements such as zirconium, copper, iron, and nickel; others combine metals with near-metalloids such as silicon, carbon, and phosphorus. Some metallic glasses are attractive for their magnetic properties; iron-boron glass, for example, is commonly used in distribution transformer cores. Here, Schroers focuses on promising opportunities stemming from BMGs' mechanical and thermodynamic properties. Specifically, BMGs exhibit a rare and tantalizing combination of traits: Their amorphous, defect-free microstructure makes them one of the strongest engineering materials known, and because they can occupy a peculiar thermodynamic middle ground between solid and liquid, they can be processed like plastics into nanoscale textures, seamless hollow containers, and other shapes that are impossible to make with traditional metals.